Morocco : Report on Observance of Standards and Codes; Fiscal Transparency Module. (IMF Staff Country Reports; Country Report ;, 2005)
This report evaluates Morocco's fiscal transparency practices and assesses compliance with the IMF's Code of Good Practices on Fiscal Transparency. Morocco's fiscal management system, which remains highly centralized, is essentially reliable and supported by legal safeguards, and adequate for steering budget performance. The far-reaching amendment of the organic law governing budget laws carried out in November 1998, the legislative and regulatory provisions that accompanied it, and the recent reforms have led to significant progress with respect to the clarity of fiscal and accounting standards and access to financial information.